STRUCTURE OF A TETRADECYLTRIMETHYLAMMONIUM BROMIDE LAYER AT THE AIR-WATER-INTERFACE DETERMINED BY NEUTRON REFLECTION - Simister, E; Lee, E; Thomas, R; Penfold, J (1992)
We have determined the structure of a layer of tetradecyltrimethylammonium bromide (C14TAB) adsorbed from solution at the air/water interface using neutron specular reflection data from several isotopic compositions. Two different methods of analysis of the data have been used, one fitting a single structural model to the set of reflectivity profiles at a given concentration, and the other using an approximate but more direct method. The relative locations of the chain, head, and water distributions across the interface have been determined directly. For the saturated monolayer (just below the critical micelle concentration (cmc)) the mean center-to-center distribution of chains and heads is found to be 7 ± 0.5 Å, that between chains and water to be 7 ± 0.5 Å, and that between heads and water 1 ± 0.5 Å. The mean thickness of the different regions is model dependent. The chain region is found to have a thickness of 17.5 ± 1 Å for a uniform layer model and 16 ± 1 Å for a Gaussian distribution (at 1/e of the height), both less than the fully extended chain length. The corresponding values for the heads are 7 ± 3 (uniform layer) and 6 ± 3 Å. At about one-third the cmc the chain region becomes thinner (Gaussian width = 12 ± 2 Å) and the mean separation of chains and water decreases to 6 Å. Above the cmc the surfactant is more closely packed and the thickness of the head-group distribution increases to 12 ± 3 Å (Gaussian profile). This is attributed to a "roughening" of the head-group part of the layer. © 1992 American Chemical Society.